Agricultural carbon credits: A pathway to environmental sustainability - Adhisankaran, Kandasamy; Manivannan, Venkatesan; Sakthivel, Nalliappan; Balachandar, Dananjeyan; Ragunath, Kaliaperumal; Vasumathi, Venkatesan (Plant Science Today, 2024)
Climate change and ensuring food security for a rapidly growing global population are two of the biggest challenges in agriculture. To meet the commitments made in the Paris Climate Agreement, it is important to use effective methods for managing soil that can help sequester and stabilise carbon. Conservation agriculture has a huge potential to sequester carbon in plants and soil, making it a viable option for carbon trading despite its significant contribution to global greenhouse gas emissions. Carbon sequestration can be achieved through sustainable practices such as adopting conservation agriculture, crop rotation, cover crop cultivation, crop residue incorporation or mulching, effective management of nutrient supply to crops, and transforming towards organic agriculture and agroforestry. These practices promote food security and environmental improvement and help mitigate global warming. Carbon pricing mechanisms are policies that impose a cost on carbon pollution, encouraging people and organisations to choose low-carbon options and reduce their emissions. Agricultural producers can benefit from carbon trading by earning extra revenue by selling their excess carbon credits to those who emit higher amounts of greenhouse gases. Carbon credit systems in agriculture are still in the early stages, so farmers may have more opportunities to participate in future carbon trading.